Iz ljubezni in zaradi ljubezni. Izražanje čustev kot vzrokov človekovih odzivov s pomočjo predložnih zvez - Będkowska-Kopczyk, Agnieszka (Jezik in slovstvo, 2020)
The article examines Slovenian constructions with the causal preposition zaradi 'because of' and the spatial prepositions od 'from', iz 'out of, and v 'in' that portray emotions as an inner cause of human behaviour. It is argued that the choice of preposition is not arbitrary but determined by conceptual and pragmatic factors. The study shows that the choice of a spatial preposition depends on whether the emotion is perceived as a controllable or uncontrollable force. In contrast, the preposition zaradi 'because of' provides an explanation of the causal relation between the emotion and the resulting event, and can therefore be used regardless of whether the emotion is perceived as controlled or not.
Keywords: causality; čustva; emotions; predlogi; prepositions; Slovenian; slovenščina; vzročnost